Postharvest Application of Abscisic Acid and Methyl Jasmonate on Fruit Quality of ‘Red Zaosu’ Pear - Yuhao Wu; Xin Zou; Shangyun Li; Chao Tang; Haoru Tang; Yong Zhang (Agronomy, 2025)
Subsequent to the harvesting of ‘Red Zaosu’ pears, a swift decline in quality becomes evident. This is characterized by the discoloration of the peel, the softening of the flesh and metabolic alterations during storage. To elucidate the regulatory roles of phytohormone in fruit preservation, postharvest pears were treated with 100 μmol/L abscisic acid (ABA), 100 μmol/L methyl jasmonate (MeJA) or their combination (ABA + MeJA). The results indicated that the phytohormone treatment groups exhibited varying degrees of efficacy in improving the postharvest quality of pear fruits. The combined treatments did not show synergistic effects, but rather inhibited anthocyanin accumulation and antioxidant enzyme (POD, CAT, APX, POD) activities and significantly reduced soluble solids, acidity and flavonoids, although peel brightness was maintained. ABA alone treatment promoted anthocyanin accumulation and peel coloring, but reduced fruit firmness, crispness, chewiness and soluble solids, enhanced total flavonoids and CAT activity and reduced malondialdehyde accumulation, while MeJA alone treatment inhibited anthocyanin synthesis and coloring, but also reduced firmness and soluble solids, and enhanced total flavonoids and CAT activity. The results indicate that ABA and MeJA exhibit differential regulatory effects on fruit quality when applied individually, and their combined application showed inferior effects compared to individual treatments. This finding provides a theoretical basis for optimizing combined phytohormone-preservation techniques.